APLIKASI PENCATATAN HEALT ALERT CARD (HAC) PADA BANDARA SULTAN THAHA JAMBI BERBASIS WEB: Kantor Kesehatan Pelabuhan (KKP);Application;Healt Alert Card (HAC);Mysql;PHP;Website. - Sany, Ezrifal; Kahar, Novhirtamely; Gustina; Halomoan Sihombing, Hanter (LP2M Universitas Nurdin Hamzah, 2021)
Recording on the standby card or the so-called Health Alert Card (HAC) is still done manually at Jambi Sulthan Thaha Airport. This makes the work less effective and efficient in terms of time to complete work in the field. Seeing these conditions, an application is needed to assist Jambi KKP (Port Health Office) officers or employees in making a policy, therefore a Website-Based Health Alert Card (HAC) data input application for passengers at the Jambi Sulthan Thaha Airport. Which will be applied to assist Jambi KKP (Port Health Office) officers or employees in carrying out their duties to the maximum. With the Web-Based Health Alert Card (HAC) Registration Application at Sulthan Thaha Airport Jambi, it is hoped that it can assist officers or employees in inputting passenger HAC data that is still manual or still recorded as Web-based data input. That way every input data that is inputted to the computer through the Website Application will produce work that is effective, efficient and fast and safe to be stored and managed properly. Making this application is done by collecting data, system design, system analysis, and database design. Making this application program developed with PHP, the database used is MySQL. Data input needs in this application are departure data, airline data, individual admin data, and departure report data.